PERCEPTIONS OF TEACHERS ABOUT THE USE OF EDUCATIONAL TECHNOLOGIES IN THE PROCESS OF INSTRUCTION - Dogan, Suleyman (FAC TEACHER EDUCATION, 2010)
Technological developments have been adapted to education. Advanced educational equipments have been integrated into the education and these equipments have always been used by the teachers in the classroom. The purpose of this study is to determine the positive and negative effects of the technological equipments on teachers. The participants of the study consisted of randomly selected 1014 primary and secondary teachers from state and private school (Female: 525, Male: 489) in Istanbul. The data was collected by Teachers Perception Scale of Educational Technology'' developed by researcher including 27 questions. The data was analyzed by using a statistical packet program. According to research results, the applications of educational technology oldie teachers (hiring academic yew; is very effective in education and it is believed that this should be developed intensively.
Keywords: teacher; instruction; education; educational technology; perception; MEDIA; Education & Educational Research